Sports video analysis and its tool development - Lim, Alvin Kar Keng. (2009)
The project is on the Image or Video Processing aspect of sports videos. The objective of this project is to use image or video processing techniques to analyze sports videos to generate information such as judging the flight of a tennis ball and where it landed on a court. The project is on the Image or Video Processing aspect of sports videos. The objective of this project is to use image or video processing techniques to analyze sports videos to generate information such as judging the flight of a tennis ball and where it landed on a court. The data collection process occupied the majority of this project. The software development process and the creation of the GUI are also important in the development of this project. The main focus of this project is to analyze 100m race videos to detect the timing that the first subject touches the finishing line. Difficulty was faced in the data collection process due to the complexity of the high speed camera capturing system.